Current state of endovascular treatment of anterior cerebral artery aneurysms - Li, Bingwei; Zhang, Kun; Yu, Jinlu (Frontiers in Neurology, 2024)
The locations of anterior cerebral artery (ACA) aneurysms vary, and various aneurysms can occur along the course of the ACA. Ruptured and some unruptured ACA aneurysms may require aggressive treatment to avoid bleeding or rebleeding. Although open surgery is an effective treatment for ACA aneurysms, endovascular treatment (EVT) is becoming an alternative treatment in select cases. EVT techniques for ACA aneurysms often vary and are performed on a case-by-case basis according to the nature and location of the aneurysm. To better understand the EVT strategy for ACA aneurysms, it is necessary to review EVT for ACA aneurysms. In this review, the following topics are discussed: ACA anatomy and anomalies, classifications of ACA aneurysms, the natural history of ACA aneurysms, open surgery and EVT statuses for ACA aneurysms, EVT techniques for various ACA aneurysms, and the prognosis and complications of EVT for ACA aneurysms. According to our review and experience, traditional coiling EVT is still the preferred therapy for most ACA aneurysms. For A1 aneurysms, EVT is challenging. After the selection of appropriate cases, deployment of a flow diverter and Woven EndoBridge device can result in a good prognosis for patients with ACA aneurysms. In addition, parent artery occlusion can be used to treat A1 aneurysms with good collateral circulation and some distal ACA aneurysms. In general, EVT is gaining popularity as an alternative treatment option for ACA aneurysms.